COMPARISON OF LEGAL PROTECTION GUARANTEE IN TRADEMARK RIGHTS IN USA AND IN INDONESIA - Prasasti Dyah Nugraheni (Faculty of Law Universitas 17 Agustus 1945 Semarang, 2020)
Trademarks in trade activities have uses as promotional tool, guarantor for quality and quantity of services and goods produced, and tool to show the origin of services and goods produced. United States of America uses registration system in process of protecting trademark rights, which guarantees legal protection of every person and every company whose trademark rights meet requirements of trading activities. Whereas Indonesia uses constitutive system in process of protecting trademark rights, which guarantees legal protection to first person and first company to register their trademark rights. In this journal, author uses a normative and juridical research method, meaning that legal writing is carried out through analysing secondary legal materials or library materials to find solutions to legal problems that arise and using a problem approach based on the law or general legal rules about protection of trademark rights that apply to present and approach to problems based on a conceptual basis. Results of writing show that United States of America uses process of fulfilling requirements for intention to carry out trade activities or use process so that its Trademark Rights are protected, whereas, Indonesia uses process of registering Trademark Rights so that its Trademark Rights are protected.